Tinjauan Literatur: Studi Ketidaklengkapan Pengisian Rekam Medis Rawat Inap Kasus Interna - Ni Made Periani; I Made Sudarma Adiputra; Ni Nyoman Meryadi (Jurnal Rekam Medis dan Informasi Kesehatan, 2020)
Completeness of medical records is very important because it affects the patient's treatment process and insurance claims. In fact, there are still many incomplete medical records. The purpose of this study was to determine the results of the completeness of filling in inpatient medical records for internal cases. The method used is a literature review method. Strategies in searching for Indonesian language studies relevant to the topic are carried out using Google Scholar. The keywords used were the study of completeness of filling in inpatient medical records for internal cases, analysis of completeness of medical records. In the search phase, journal articles are limited to publications from 2015-2020. Identification review on entry and exit summary form and anesthesia report was 99%. Review important reports on the return summary form 88.89%. Authentication Review is 60%. Documenting that is not correct on the disease course sheet 36.11%. The results of journal analysis show that the completeness of medical records has not reached 100% and there are still many incomplete items. Suggestions for doctors and nurses to better understand the importance of completeness of medical records, especially the completeness of the medical resume form. ABSTRAKKelengkapan rekam medis sangat penting karena berpengaruh terhadap proses pengobatan pasien dan klaim asuransi. Kenyataan masih banyak rekam medis yang belum terisi lengkap. Tujuan dari penelitian ini adalah untuk mengetahui hasil kelengkapan pengisian rekam medis Rawat inap kasus interna. Metode yang digunakan adalah metode telaah literature review. Strategi dalam pencarian studi berbahasa Indonesia yang relevan dengan topik dilakukan dengan menggunakan Google Scholar. Kata kunci yang digunakan adalah studi kelengkapan pengisian rekam medis rawat inap kasus interna, analisis kelengkapan rekam medis. Pada tahap pencarian artikel jurnal dibatasi terbitan dari tahun 2015-2020. Hasil review identifikasi pada formulir ringkasan masuk dan keluar serta laporan anastesi yaitu 99%. Hasil review laporan penting pada formulir ringkasan pulang 88,89%. Hasil review Autentifikasi yaitu 60%. Pendokumentasian yang tidak benar pada lembar perjalanan penyakit 36,11%. Hasil analisis jurnal menunjukkan bahwa Kelengkapan rekam medis belum mencapi 100% dan masih banyak terdapat item yang tidak lengkap. Saran bagi dokter dan perawat agar lebih memahami petingnya kelengkapan rekam medis terutama kelengkapan pada formulir resume medis.